Targeting Different Monocyte/Macrophage Subsets Has No Impact on Outcome in Experimental Stroke. Issue 4 (April 2017) - Schmidt, Antje; Strecker, Jan-Kolja; Hucke, Stephanie; Bruckmann, Nils-Martin; Herold, Martin; Mack, Matthias; Diederich, Kai; Schäbitz, Wolf-Rüdiger; Wiendl, Heinz; Klotz, Luisa; Minnerup, Jens
Abstract : Background and Purpose—: Peripheral immune cell infiltration contributes to neural injury after ischemic stroke. However, in contrast to lymphocytes and neutrophils, the role of different monocyte/macrophage subsets remains to be clarified. Therefore, we evaluated the effects of selective and unselective monocyte/macrophage depletion and proinflammatory (M1-) and anti-inflammatory (M2-) macrophage transfer on the outcome after experimental cerebral ischemia. Methods—: To assess short-term effects of monocytes/macrophages in acute ischemic stroke, mice underwent transient middle cerebral artery occlusion and received either clodronate liposomes for unselective macrophage depletion, MC-21-antibody for selective depletion of proinflammatory Ly-6C high monocytes, or proinflammatory (M1-) or anti-inflammatory (M2-) macrophage transfer. In addition, the impact of MC-21-antibody administration and M2-macrophage transfer on long-term neural recovery was investigated after photothrombotic stroke. Neurobehavioral tests were used to analyze functional outcomes, infarct volumes were determined, and immunohistochemical analyses were performed to characterize the postischemic inflammatory reaction. Results—: Selective and unselective monocyte/macrophage depletion and M1- and M2-macrophage transfer did not influence tissue damage and neurobehavioral outcomes in the acute phase after middle cerebral artery occlusion. Beyond, selective depletion of Ly-6C high monocytes and M2-macrophage transfer did not have an impact on neural recovery after photothrombotic stroke. Conclusions—: Targeting different monocyte/macrophage subsets has no impact on outcome after ischemic stroke in mice. Altogether, our study could not identify monocytes/macrophages as relevant therapeutic targets in acute ischemic stroke. Abstract : Supplemental Digital Content is available in the text.